HLA class II antigens associated with systemic lupus erythematosus in black South Africans. Issue 8 (August 1995) - Rudwaleit, M; Tikly, M; Gibson, K; Pile, K; Wordsworth, P
Abstract : OBJECTIVE--To assess the associations of HLA class II antigens with systemic lupus erythematosus (SLE) in black South Africans. METHODS--HLA-DRB1 genotype frequencies assigned by polymerase chain reaction (PCR) amplification and sequence specific oligonucleotide probes were compared between 49 black SLE patients from Baragwanath Hospital and 87 ethnically matched controls. HLA-DQA1 and -DQB1 genotypes were also assigned in 45 of the SLE patients and 74 controls by PCR using sequence specific primers. RESULTS--HLA-DRB1*02 was increased in the patients compared with controls (odds ratio = 3.67; 95% confidence interval = 1.49 to 9.02; p < 0.005). HLA-DQB1*0201 was not associated with development of the disease itself, but was associated with the presence of Ro antibodies (p = 0.01). HLA-DRB1*03 was less strongly linked to DQB1*02 in this population than in white populations and was not associated with SLE. CONCLUSIONS--In black South Africans there is evidence for a locus on DR2 haplotypes contributing to SLE. Another gene, possibly HLA-DQB1*02, not linked to DR2 is involved in the subset of patients exhibiting Ro antibodies.